Emergent Treatment of Acute Cholangitis and Acute Cholecystitis - Navuluri, Rakesh; Hoyer, Matthew; Osman, Murat; Fergus, Jonathan (Seminars in Interventional Radiology, 2020)
Acute pathology of the biliary tract including cholangitis and cholecystitis can lead to biliary sepsis if early decompression is not performed. This article provides an overview of the presenting signs and symptoms and role of interventional radiology in the management of patients with acute cholangitis or acute cholecystitis. It is especially important to understand the role of IR in the context of other treatment options including medical management, endoscopy, and surgery.
Keywords: cholangitis; cholecystitis; interventional radiology; biliary drainage